Communication Deficit and Monetization of Political Contests at the Electoral Commission of Ghana - Shadrack Bentil; Edmund Poku Adu (Department of Government Studies Universitas Muhammadiyah Makassar, 2019)
The current state of the office of the Electoral Commission (EC) of Ghana can be couched as a bleeding pillar in Ghana’s electoral democracy pending crisis. In spite of the numerous reform measures undertaken by the EC to improve the quality delivery of its constitutional mandate, communication deficit and the increasing monetization of parliamentary and presidential contestation poses a serious threat to broader participation and competition in Ghana's future electoral fortune. Thus, the objective of the paper was to interrogate the issues of communication inefficiencies and monetization of political contestations by the Electoral Commission of Ghana and proffer pragmatic solutions that can be taken into consideration in years ahead due to the past and recent experiences of neighbouring countries within the sub-region. The study employed the qualitative research methodology to elicit responses from 12 experts in the field of elections. Apart from the primary data generated from the field, secondary sources were consulted to situate the discussion in the existing debate in the literature. The findings of the study revealed that monetization of the political contest has negative implications for a competitive political contest–disqualification of citizens with capable minds from contesting in a multi-party democracy) whilst communication deficit was found to be deepening public distrust in the Electoral Commission of Ghana. The study, therefore, recommended among others the creation of a three-man office solely responsible for managing the commission's website and other electronic outlets, and the immediate activation and implementation of the provision in the 2020 Strategic Plan of the Electoral Commission which has remained dormant after 2016 elections.